MANAJEMEN LABA AKRUAL DAN RIIL SEBELUM DAN SETELAH ADOPSI WAJIB IFRS DI UNI EROPA - Yayu Putri Senjani (Faculty of Economic and Business, 2013)
This study aims to provide empirical evidence on earnings management practices in the Europe Union in three years before and after the mandatory IFRS adoption. Earning management practices what are observed is accrual earnings management (the level of discretionary accruals) and real earnings management (abnormal cash flow from operation and abnormal production costs). Data is retrieved from OSIRIS database by using the purposive sampling method and was tested with paired sample t-test. The results showed empirically that there is no difference between accrual and real earnings management in the period before and after the mandatory IFRS adoption. Other results also showed that accruals and real earnings management are positively correlate for abnormal production costs after the mandatory IFRS adoptionDOI: 10.15408/etk.v12i1.1905